PENGARUH KEPERCAYAAN DIRI TERHADAP KECEMASAN DALAM MENGHADAPI DUNIA KERJA PADA MAHASISWA SEMESTER AKHIR PROGRAM STUDI FARMASI UNIVERSITAS SARI MUTIARA INDONESIA - Indo Mora; Siska Dwi Ningsih; Sri Ramadhani; Klarita Cerah Tafona (Psikologi Universitas Sari Mutiara Indonesia, 2021)
Anxiety arises when individuals are faced with certain situations that threaten themselves. This anxiety arises from the assumption that because they are not sure of their competence, they are one of the factors causing the emergence of fear and worry in final semester students about the possibility of getting a job that creates a feeling of insecurity. This study aims to see the effect of self-confidence on anxiety facing the world of work in final semester students at the Pharmacy Study Program, Sari Mutiara University, Indonesia. The type of research used is quantitative research. It is called quantitative because the research data is in the form of numbers and data analysis uses statistics. The samples taken in this study were students of the Pharmacy Study Program, Universitas Sari Mutiara Indonesia class of 2017 who were in the process of working on a thesis with a total of 60 people. Based on the results of the study, the value of R = 0.75 indicates the relationship between the variables of self-confidence and anxiety in dealing with the world of work in the final semester students of the pharmacy study program at Sari Mutiara University, Indonesia. The value of R square = 0.06, the number has a meaning of 0.6% while the remaining 94% is influenced by other factors. High self-confidence in students in the final semester of the pharmacy study program does not have an effect on anxiety in dealing with the world of work.